Students’ Learning Strategies in Oral Productions Across Speaking Proficiencies - Amin, Yohana Rosmeritati; Sulistyo, Teguh; Weganofa, Riza; Herawati, Siane (Journey: Journal of English Language and Pedagogy, 2024)
Speaking skills are generally perceived as the measurement of the success of English Language Teaching (ELT), yet these skills are considered very hard to achieve. In fact, there have been different levels of speaking proficiencies among students. Therefore, the purpose of this study was to investigate the oral production learning strategies used by high and low proficiency English Education students. The design of this study was descriptive qualitative. The third semester English Education students of Universitas PGRI Kanjuruhan Malang were included. In collecting the data, the researchers used three instruments, especially a speaking test, documentation, questionnaires, and interview. The results show that the students with high speaking proficiency have higher motivation and use all kinds of strategies in the same frequency. Meanwhile, the students with low speaking proficiency use metacognitive, cognitive, and memory strategies. However, they did not use these strategies with the same frequency, where the lowest percentage of strategies used were affective and compensatory. The results suggest that students should choose learning strategies based on their needs. Students should use all learning strategies to improve their speaking skills. The implications and suggestions of the research are also discussed.